2014
DOI: 10.1016/j.scitotenv.2014.06.090
|View full text |Cite
|
Sign up to set email alerts
|

A mini-review on the impacts of climate change on wastewater reclamation and reuse

Abstract: To tackle current water insecurity concerns, wastewater reclamation and reuse has appeared as a promising candidate to conserve the valuable fresh water sources whilst increasing the efficiency of material utilization. The climate change, nevertheless, poses both opportunities and threats to the wastewater reclamation industry. Whereas it elevates the social perception on water-related issues and fosters an emerging water-reuse market, the climate change simultaneously presents adverse impacts on the water rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(23 citation statements)
references
References 69 publications
(87 reference statements)
0
23
0
Order By: Relevance
“…Rising temperatures are also expected to increase the incidence of diarrheal disease (Hutton and Chase, 2016). Climate factors determine the number, type, virulence and infectivity of pathogens transmitted through water or vectors that breed in water, and thus they may impact the associated infectious diseases (Vo et al, 2014). Increased precipitation intensity will create peak concentrations of pathogens in waterways due to sewage overflow and runoff (Vo et al, 2014).…”
Section: Climate Changementioning
confidence: 99%
See 1 more Smart Citation
“…Rising temperatures are also expected to increase the incidence of diarrheal disease (Hutton and Chase, 2016). Climate factors determine the number, type, virulence and infectivity of pathogens transmitted through water or vectors that breed in water, and thus they may impact the associated infectious diseases (Vo et al, 2014). Increased precipitation intensity will create peak concentrations of pathogens in waterways due to sewage overflow and runoff (Vo et al, 2014).…”
Section: Climate Changementioning
confidence: 99%
“…Climate factors determine the number, type, virulence and infectivity of pathogens transmitted through water or vectors that breed in water, and thus they may impact the associated infectious diseases (Vo et al, 2014). Increased precipitation intensity will create peak concentrations of pathogens in waterways due to sewage overflow and runoff (Vo et al, 2014). Increased groundwater flows and levels due to more rainfall and frequent or larger floods promote the spread of pathogens through greater mobility and survival, and greater saturation of soil increases pathogen survival (Charles et al, 2009).…”
Section: Climate Changementioning
confidence: 99%
“…Water reuse applications for irrigation, toilet flushing, and clothes washing for the hypothetical community in the DES+MBR applications were consistently the most effective across the three impact categories examined. While studies have already shown the environmental favorability of district heating systems compared to conventional systems [6,26], research in community-based wastewater treatment and reuse is at an early stage of development [28,47]. The reduction in impacts from sewage-heat-recovery-based district heating systems can yield additional environmental savings with community-based wastewater treatment and water reuse, particularly when a greater volume of wastewater is used in the process.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the low cost of construction and maintenance and that wetland ecosystems are among the most endangered ecosystems worldwide [1], our results suggest the importance of adding natural wetland systems to traditional wastewater treatment plants in order to improve released water quality. Furthermore, reducing water consumption as a measure of conservation of available water resources for the future in response to measures imposed by climate change leads to a proportional reduction in the volume of wastewater effluent, but not in the contaminant loading [48]. Thus, more efficient wastewater treatment plants are necessary, which might be achieved by coupling natural wetland systems to traditional treatment plants, avoiding economic and ecological problems at the same time.…”
Section: Discussionmentioning
confidence: 99%